2009
DOI: 10.1038/ni.1824
|View full text |Cite|
|
Sign up to set email alerts
|

Recognition of RNA virus by RIG-I results in activation of CARD9 and inflammasome signaling for interleukin 1β production

Abstract: Interleukin 1 beta (IL-1 beta) is a potent proinflammatory factor during viral infection. Its production is tightly controlled by transcription of Il1b dependent on the transcription factor NF-kappaB and subsequent processing of pro-IL-1 beta by an inflammasome. However, the sensors and mechanisms that facilitate RNA virus-induced production of IL-1 beta are not well defined. Here we report a dual role for the RNA helicase RIG-I in RNA virus-induced proinflammatory responses. Whereas RIG-I-mediated activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
449
6
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 477 publications
(476 citation statements)
references
References 50 publications
15
449
6
6
Order By: Relevance
“…It has been demonstrated that rhabdovirus VSV infection in murine DCs induces RIG-1-dependent production of IL-1b and IL-18 via NF-jB, caspase-1, and caspase-3 activation; thus, RIG-1 is an inflammasome activator. Furthermore, DCs from RIG-1 knockdown mice are not able to secrete IL-1b [95]. However, the results of this study conflict with that of another report, which demonstrated that VSV is recognised by NLRP3 and not by RIG-1 [46].…”
Section: Rig-1contrasting
confidence: 99%
“…It has been demonstrated that rhabdovirus VSV infection in murine DCs induces RIG-1-dependent production of IL-1b and IL-18 via NF-jB, caspase-1, and caspase-3 activation; thus, RIG-1 is an inflammasome activator. Furthermore, DCs from RIG-1 knockdown mice are not able to secrete IL-1b [95]. However, the results of this study conflict with that of another report, which demonstrated that VSV is recognised by NLRP3 and not by RIG-1 [46].…”
Section: Rig-1contrasting
confidence: 99%
“…Infl ammasome is formed with the participation of certain pattern recognition receptors and senses various danger signals (Martinon et al, 2002;Agostini et al, 2004;Mariathasan et al, 2004;Poeck et al, 2010). As a large protein complex, infl ammasome controls the activation of the proteolytic enzyme caspase-1 through the apoptosis-associated speck-like protein containing a CARD (ASC), which subsequently regulates the maturation of the pro-inflammatory cytokines interleukin-1β (IL-1β) and IL-18 (Agostini et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…IL‐1β that is produced from activated macrophages and helper T cells is an important cytokine indicator of inflammatory response 30, 31, 32, 33. The serum samples were collected from the live mice above at predetermined points for 72 h after the IV injection of PBS, HBVC (50 µg), and ABP‐HBVC (50 µg), as described in Figure 4 A.…”
Section: Resultsmentioning
confidence: 99%